2013
DOI: 10.1021/ja411742c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monofunctional Platinum Agents on Bacterial Growth: A Retrospective Study

Abstract: The effect of the novel and potent monofunctional platinum(II) agent phenanthriplatin on Escherichia coli and bacteriophage λ lysogens is reported. E. coli filamentation was observed by light microscopy when cells were grown in the presence of phenanthriplatin, cis-[Pt(NH3)2(Am)Cl]+ where Am is phenanthridine. Treatment of lysogenic bacteria with this compound resulted in lysis and the production of viral particles, as indicated by plaque formation in a bacterial lawn. The results obtained with phenanthriplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 16 publications
5
68
0
Order By: Relevance
“…The interaction of phenanthriplatin with DNA in Escherichia coli provided further evidence to support the hypothesis that DNA is the ultimate biological target of this anti-cancer agent (figure 4). Unlike monofunctional platinum(II) complexes with little or no anti-cancer activity, phenanthriplatin was able to replicate the filamentous growth morphology that cisplatin induces in E. coli [40]. This phenotype arises from induction of the bacterial SOS response as a result of DNA damage.…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexmentioning
confidence: 98%
“…The interaction of phenanthriplatin with DNA in Escherichia coli provided further evidence to support the hypothesis that DNA is the ultimate biological target of this anti-cancer agent (figure 4). Unlike monofunctional platinum(II) complexes with little or no anti-cancer activity, phenanthriplatin was able to replicate the filamentous growth morphology that cisplatin induces in E. coli [40]. This phenotype arises from induction of the bacterial SOS response as a result of DNA damage.…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexmentioning
confidence: 98%
“…275,276 Studies with Escherichia coli resembling those conducted by Rosenberg, showed that akin to cisplatin treatment, phenanthriplatin induced filamentous cell growth. 277 Monofunctional platinum(II) complexes with little biological activity in cultured cancer cells were not able to replicate this result. Phenanthriplatin-mediated filamentous E. coli growth resulted from the bacterial SOS response, indicative of DNA damage.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Differementioning
confidence: 99%
“…Phenanthriplatin maintains a spectrum of activity that is distinct from that of any other platinum agent tested in the NCI60 human tumor cell line anticancer drug screen and is 7-40 times more potent than cisplatin. The complex interacts covalently with DNA, presumably at the nucleophilic N7 position of guanine, and inhibits transcription by RNA polymerase II (18,20,21). Phenanthriplatin contains a center of chirality and can therefore form diastereomeric adducts with DNA.…”
Section: Significancementioning
confidence: 99%